2012
DOI: 10.1002/mc.21984
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the formation of lipid raft‐associated Rac1/PI3K/Akt signaling complexes by curcumin inhibits SDF‐1α‐induced invasion of human esophageal carcinoma cells

Abstract: Stromal cell-derived factor-1α (SDF-1α) is a ligand for C-X-C chemokine receptor type 4 (CXCR4), which contributes to the metastasis of cancer cells by promoting cell migration. Here, we show that the SDF-1α/CXCR4 axis can significantly increase invasion of esophageal carcinoma (EC) cells. We accomplished this by examining the effects of CXCR4 knockdown as well as treatment with a CXCR4-neutralizing antibody and the CXCR4-specific inhibitor AMD3100. Curcumin suppressed SDF-1α-induced cell invasion and matrix m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 69 publications
(107 reference statements)
5
39
0
Order By: Relevance
“…We show that MT1‐MMP stimulates cell invasion through the recruitment and activation of its effector MMP2. Furthermore, while previous studies have reported activation of MMP2 by RAC1 (Binker et al., ; Lin et al., ), here we demonstrate, for the first time, that MT1‐MMP promotes melanoma cell motility by activating MMP2, which in turn triggers RAC1 leading to an MT1‐MMP/MMP2/RAC1 signaling cascade that controls melanoma cell dissemination.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We show that MT1‐MMP stimulates cell invasion through the recruitment and activation of its effector MMP2. Furthermore, while previous studies have reported activation of MMP2 by RAC1 (Binker et al., ; Lin et al., ), here we demonstrate, for the first time, that MT1‐MMP promotes melanoma cell motility by activating MMP2, which in turn triggers RAC1 leading to an MT1‐MMP/MMP2/RAC1 signaling cascade that controls melanoma cell dissemination.…”
Section: Discussionsupporting
confidence: 69%
“…We show that MT1-MMP stimulates cell invasion through the recruitment and activation of its effector MMP2. Furthermore, while previous studies have reported activation of MMP2 by RAC1 (Binker et al, 2010;Lin et al, 2012), here we demonstrate, for the first time, that MT1-MMP promotes melanoma cell motility by activating MMP2, which in turn triggers RAC1 leading to an MT1-MMP/MMP2/RAC1 signaling cascade that controls melanoma cell dissemination. Interestingly, a recent study by Scott et al (2011) showed that primary melanomas express genes that are correlated with metastatic potential and that these metastasis drivers can be predictive of patient outcome.…”
Section: Discussionsupporting
confidence: 63%
“…Lipid raft disruption impairs the Akt signaling pathway in epidermal keratinocytes [40]. Suppressing the formation of raft-associated Akt inhibits SDF-1α-induced invasion of esophageal carcinoma cells [41]. In the present study, we demonstrated that SDF-1α-induced platelet aggregation and Akt phosphorylation are inhibited by the raft disrupting agent MβCD.…”
Section: Discussionsupporting
confidence: 56%
“…Curcumin prevents human colon cancer, colo-205 cells migration through the inhibition of NFκB/p65 and downregulation of cyclooxygenase-2 and MMP-2 expression [178] . Lin et al [179] reported that curcumin inhibits SDF-1α-induced invasion of human esophageal carcinoma cells by down regulating MMP-2 promoter activity as well as suppressing the formation of lipid raft-associated Rac1/PI3K/Akt signaling complexes. In conclusion, curcumin appears to have a significant potential in the treatment of multiple diseases that are due to oxidative stress.…”
Section: Curcuminmentioning
confidence: 99%